Exploring the Impact of Teacher Performance Evaluation Systems:A Comparative Analysis of Public VS Private Secondary Schoolsand Their Role in Shaping Educational Quality (Journal of Asian Development Studies, 2024)
The present study compared teachers' performance evaluation practices of public and privatesector schools at the secondary level. The study's objectives were to examine the performanceevaluation practices at public and private sector secondary schools and to compare theperformance evaluation practices between public and private sector schools at the secondarylevel. The study's target population was public and private sector secondary school head teachersand teachers. One hundred schools were selected through a random sampling technique. Datawere collected from 100 head teachers and 329 teachers to examine and compare the performanceevaluation practices at secondary schools. Based on the literature review, an instrument wasdeveloped. The reliability coefficient of the instrument was found to be 0.898. Data were collectedpersonally and analyzed by using SPSS. Headteachers' and teachers' opinions were solicited on afive-point Likert scale. The Chi-square test was applied to compare the responses of head teachersand teachers from public and private secondary schools. It was found that in both public andprivate schools, the most commonly used practices for the performance evaluation of teacherswere "how they maintain their teacher's diary, their punctuality, their contribution towardsorganizing the sports and co-curricular activities, organization of games, by taking feedback fromcolleagues, by visiting their classrooms and from the result of the students in exams.